A Case of Descemet’s Membrane Endothelial Keratoplasty in a failed Penetrating Keratoplasty - Singh, Sanjay Kumar; Yadav, Reena; Sharma, Ashmita (Nepalese Journal of Ophthalmology, 2018)
Background: Descemet’s membrane endothelial keratoplasty (DMEK) is an evolving option for failed penetrating keratoplasty (PK) as it has shown promising results compared to repeat PK. Case description: A 22 years young gentleman presented with gradual diminution of vision in the left eye (LE) for six months following therapeutic PK for a perforated fungal corneal ulcer. His best spectacle corrected visual acuity (BSCVA) was 6/60 in LE. Slit-lamp examination of LE revealed circumcorneal congestion with full thickness corneal graft with micro and macrobullae, diffuse stromal edema, DM folds and seven well-buried sutures. Intraocular pressure was 20 mmHg in the right eye whereas it could not be assessed in the left eye. The diagnosis of LE failed PK was made and the patient underwent DMEK. At four months postoperative follow up visit, BSCVA improved to 6/9. This is the first reported case of DMEK after a failed PK in a young patient from Nepal which was successfully treated without any complications. Conclusion: DMEK has a higher potential for better visual rehabilitation compared to DSEK and PK. It has also proved its efficacy in the treatment of endothelial graft failure following PK as it is a less invasive procedure.